The functions of urban design social attributes in creative placemaking: the case of Kuala Lumpur event festivals - Ramli, Nurul Atikah; Ujang, Norsidah (Emerald Publishing, 2021)
Purpose – An increasing effort to reinforce cultural and social activities in creative placemaking is observed. Despite extensive previous studies, works of literature ignored the necessary group-specific indicators and processes in creative placemaking. In successful placemaking, the vital attributes of a place as a social platform should be identified and intensified in the initiatives taken. As such, this study aims to examine the functions of urban design social attributes in generating meaningful creative placemaking initiatives. Design/methodology/approach – A survey was performed, which involved 340 visitors in the inner city of Kuala Lumpur, Malaysia, from one case study (a strategic social event initiative called RIUH) on users’ preference toward the social attributes of place and the factors influencing preference. Field observations were carried out to understand the social activities and pattern of engagement. Findings – The preference study revealed that urban design social attributes encompassed the essential inclusiveness, value, diversity and vitality of place because of high preference and a significant difference among groups. Social implications – Understanding users’ preferences has emphasized the relevance of each urban design social attribute in accommodating different user opportunity groups, ultimately inducing a positive social impact in creative placemaking. Originality/value – This study demonstrated the success of creative placemaking in urban development from the social dimension. It provides an understanding that the priority of creative practices should be redirected toward a more in-depth approach in addressing individuals, social capacity, involvement and wellbeing through the optimization of benefits and other creative placemaking values.